SYNTHESIS OF PRIMITIVE MATRICES OVER A FINITE GALOIS FIELDS AND THEIR APPLICATIONS (Journal of Information Technologies in Education (ITE), 2012)
The algorithms for constructing generalized primitive matrices Galois and Fibonacci arbitrary order , the items belong to the prime field , . The examples of application of these matrices in the problems of the synthesis of generalized linear shift register with linear feedback and matrix analogue Diffie-Hellman.
Keywords: generators of pseudorandom sequences; irreducible and primitive polynomials; primitive matrices; protocol exchange encryption keys